2017
DOI: 10.18632/oncotarget.17676
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and economic factors are associated with weight gain between before and after cancer diagnosis: results from the prospective population-based NutriNet-Santé cohort

Abstract: PurposeWhile many cancer patients are affected by weight loss, others tend to gain weight, which may impact prognosis and risk of recurrence and of second cancer. The aim of this prospective study was to investigate weight variation between before and after cancer diagnosis and socio-demographic, economic, lifestyle and clinical factors associated with moderate-to-severe weight gain.Methods1051 incident cases of first primary cancer were diagnosed in the NutriNet-Santé cohort between 2009 and 2015. Weight was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
3
5
0
1
Order By: Relevance
“…We also observed that breast cancer patients were more inclined to practice weight‐loss restrictive diets. This is consistent with the fact that weight gain is more frequent for this cancer location, as shown in a previous study within the NutriNet‐Santé cohort and in other studies . Dieting patients were also more likely to use dietary supplements, probably with the overall intention to take charge of their own health and to adopt (supposed) healthy behaviors …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed that breast cancer patients were more inclined to practice weight‐loss restrictive diets. This is consistent with the fact that weight gain is more frequent for this cancer location, as shown in a previous study within the NutriNet‐Santé cohort and in other studies . Dieting patients were also more likely to use dietary supplements, probably with the overall intention to take charge of their own health and to adopt (supposed) healthy behaviors …”
Section: Discussionsupporting
confidence: 91%
“…However, no study previously provided descriptive information on the proportion of cancer patients practicing weight‐loss restrictive diets and their associated profiles. In the French NutriNet‐Santé cohort as well as in other studies, it has been shown that while some cancer patients tend to lose weight after their cancer diagnosis, a substantial proportion gains weight, especially women with breast cancer. Furthermore, excess weight is recognized as a risk factor for a poorer prognosis, and higher risk of recurrence, second cancer or mortality, thus, attaining or maintaining a normal body weight is recommended for cancer survivors .…”
Section: Introductionmentioning
confidence: 88%
“…This captures economic stability in a more pragmatic way than demographic data alone; data such as income and employment do not account for variables such as debt or family support. Sella et al provide substantial evidence of the association between financial need and weight gain in young breast cancer survivors in the United States, supporting the results from prior hypothesis‐generating retrospective and/or international studies 8,9 . The results of this prospective study by Sella and colleagues also provide evidence that there is not a significant association between posttreatment weight gain and receipt of contemporary breast cancer‐directed therapies, including those inducing premature amenorrhea, which has been long‐debated in the literature 10 …”
supporting
confidence: 63%
“…As to the medical dimension, a lower SES is generally associated with a lower use of cancer screening services ( 71 , 72 ) and a higher mortality ( 73 ). As to the determinants of behaviors, sociodemographic and economic factors influence the risk of weight gain after cancer, which may impact prognosis and risk of recurrence and of second cancer ( 74 ). As to the workplace environment, persons with a lower SES have physically heavier jobs with lower levels of autonomy and more temporary contracts ( 13 , 75 ).…”
Section: Discussionmentioning
confidence: 99%